2018
DOI: 10.1002/smr.1954
|View full text |Cite
|
Sign up to set email alerts
|

Scaling agile in large organizations: Practices, challenges, and success factors

Abstract: Context: Agile software development has nowadays reached wide adoption. However, moving agile to large‐scale contexts is a complex task with many challenges involved. Objective: In this paper, we review practices, challenges, and success factors for scaling agile both from literature and within a large software company, identifying the most critical factors. Method: We conduct a focused literature review to map the importance of scaling practices, challenges, and success factors. The outcome of this focused li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
113
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(164 citation statements)
references
References 95 publications
5
113
0
1
Order By: Relevance
“…Previous research has dealt with the implications of the adoption of agile structures in non-digital born enterprises for the organizational design, including challenges and success factors when implementing agile methods [3,8,9]. Non-digital born enterprises encompass companies that do not have digital technologies at the core of their business model [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has dealt with the implications of the adoption of agile structures in non-digital born enterprises for the organizational design, including challenges and success factors when implementing agile methods [3,8,9]. Non-digital born enterprises encompass companies that do not have digital technologies at the core of their business model [10].…”
Section: Introductionmentioning
confidence: 99%
“…Non-digital born enterprises encompass companies that do not have digital technologies at the core of their business model [10]. Also, the process by which scaled-agile frameworks are implemented within those type of enterprises itself has been investigated recently [8]. However, these works either emphasize the roles of specific framework templates (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…ADM offer disciplined, yet lightweight processes while placing human effort and experience at the core through its central focus on people and interactions (Hoda et al 2018). Therefore, the importance of the people factor for the success of ADM projects has been constantly highlighted in the scholarly literature (Cockburn and Highsmith 2001;Boehm and Turner 2005;Moe et al 2012;Fortmann 2018;Cram 2019) and it has been repeatedly identified as critical success factor for ADM managed projects (Lindvall et al 2002;Chow and Cao 2008;Pedersen 2013;Kalenda et al 2018). Recognizing the importance of the people factor, scholars have made considerable effort to examine human related challenges that occur in agile teams.…”
Section: Introductionmentioning
confidence: 99%
“…These practices form the foundation for the implementation of all frameworks. Only [9] conducted a comparison on practice level so far and identified eight common scaling practices by comparing LeSS and SAFe. If Scaling Agile Frameworks were compared directly in related work, the comparison was along characteristics of the frameworks [10][11][12].…”
Section: Introductionmentioning
confidence: 99%